2018
DOI: 10.1111/1365-2435.13214
|View full text |Cite
|
Sign up to set email alerts
|

The developmental environment modulates mating‐induced aggression and fighting success in adult female Drosophila

Abstract: Competition over access to resources early in life can influence development, and, in turn, affect competitive phenotypes in reproductive adults. Theory predicts that competition between adult females should be especially context‐dependent, because of constraints imposed by high costs of reproduction. However, the potential impact of developmental environments on competition in adult females remains little understood. In Drosophila melanogaster , the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 76 publications
(166 reference statements)
1
36
1
Order By: Relevance
“…The increase in female aggression 2-4 hours after mating also appears to occur in conjunction with the stimulation of ovulation (1.5 hours after mating starts) and potentially also with the beginning of egg laying (~3 hours after the start of mating) [26,60]. We have previously shown that the production of eggs is not necessary for mating-induced female aggression and our results from both the timing and genotype experiments lend support to this idea [11,48].…”
Section: Plos Onesupporting
confidence: 76%
See 1 more Smart Citation
“…The increase in female aggression 2-4 hours after mating also appears to occur in conjunction with the stimulation of ovulation (1.5 hours after mating starts) and potentially also with the beginning of egg laying (~3 hours after the start of mating) [26,60]. We have previously shown that the production of eggs is not necessary for mating-induced female aggression and our results from both the timing and genotype experiments lend support to this idea [11,48].…”
Section: Plos Onesupporting
confidence: 76%
“…There is previous evidence, however, that shows that female aggression can vary in magnitude based on qualities of the male ejaculate. Females raised at different larval densities showed different levels of increase in aggression after mating [48]. Females raised…”
Section: Genotypesmentioning
confidence: 98%
“…Interestingly, Wang et al (2020a) also noted differences in the depolarization of pC1d and pC1e following activation of the sex-peptide abdominal ganglion neuron. While these are not as extensive as seen in pC1a, they may provide a neural basis for the reported effect of mating status on female aggressive behavior (Bath et al, 2020(Bath et al, , 2018Ueda and Kidokoro, 2002).…”
Section: Involvement Of Pc1d In Female Aggression and Connections To mentioning
confidence: 92%
“…In D. melanogaster , males have strong intrasexual competition over mating and allocate considerable time and effort to court available females, while females are able to re‐mate with multiple males (Dow & Schilcher, ; Markow, ; Pitnick, ). Although intrasexual competition is mostly observed in males, aggression between females is also present, mainly when food sources are scarce (Bath et al, ; Bath, Morimoto, & Wigby, ; Ueda & Kidokoro, ). Furthermore, both males and females of this species exhibit mate choice but the degree and direction of these choices can differ depending on the population of origin and the social environment (Byrne & Rice, ; Edward & Chapman, , ; Gowaty, Steinichen, & Anderson, ; Monier, Nöbel, Isabel, & Danchin, ).…”
Section: Introductionmentioning
confidence: 99%